Control of Vascular Streak Dieback Disease of Cocoa with Flutriafol Fungicides - Febrilia Nur'aini (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Vascular streak dieback caused by the fungus Oncobasidium theobromae is one of the important diseases in cocoa crop in Indonesia. One approach to control the disease is by using fungicides. The aim of this research was to determine the effect of class triazole fungicides to the intensity of the vascular streak dieback disease on cocoa seedling phase, immature and mature cocoa. Experiments were conducted in Kotta Blater, PTPN XII and Kaliwining, Indonesian  Coffee and Cocoa Research Institute. Flutriafol 250 g/l with a concentration 0,05%, 0,1% and 0,15% foliar sprayed on cocoa seedlings, immature and mature cocoa. Active compound combination of Azoxystrobin and Difenoconazole with 0,1% concentration used as a comparation fungicides. The result showed that Flutriafol with 0,05%, 0,1% and 0,15% concentration and Azoxystrobin & Difenoconazol with 0,1% concentration could suppress the vascular streak dieback disease on seedlings. On immature plants, the application of Flutriafol was not effectively suppress the vascular streak dieback disease whereas the fungicide comparison could suppress with the efficacy level of 46.22%. On mature plants,both of fungicides could not suppress the vascular streak dieback disease. Key words: Fungicide, cocoa, vascular streak dieback, triazole, flutriafol, azoxystrobin+difenoconazol